Worker Capture in the Precarious Work Era: Reducing Turnover without Employee Commitment and Job Security - St-Denis, Xavier (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2023)
AbstractThis paper argues that employee retention remains a key priority for many employers, even as they become less likely to offer stable employment. In the face of increased job insecurity, researchers have shown that workers have adopted personalized career progression strategies that emphasize inter-firm mobility. Such strategies heighten employer concerns about employee turnover. The paper argues that the industrial relations literature would gain from closer study of organizational practices that restrict employee mobility, i.e., “worker capture strategies.” Such practices stand out from other mobility-reducing ones because they are unilateral and aim to reduce turnover without necessarily fostering a sense of commitment or loyalty among employees.SummaryThe literature on precarious work has focused on the higher frequency of layoffs and downsizing and the shift away from the standard employment relationship over the past few decades. This paper argues that employee retention remains nonetheless a key priority for many employers, even as they become less likely to offer stable employment. In the face of increased job insecurity, researchers have shown that workers have adopted individualized career progression strategies in which inter-firm mobility plays a great role. Such strategies heighten employer concerns about employee turnover. This paper reviews the state of the literature on organizational practices that address employer concerns about employee retention. It then argues that this literature would gain from closer study of organizational practices that restrict employee mobility, which it labels “worker capture strategies.” They include non-compete and non-solicitation clauses in employment contracts, no-poaching agreements between firms, and TRAP clauses. Such practices stand out from others because of their one-sided nature and their use as a turnover reduction strategy that does not necessarily drive a sense of commitment or loyalty among employees.